Corporate governance and firm performance: evidence from top 30 public listed companies in Malaysia / Nur Dhaniah Mohd Noh - Mohd Noh, Nur Dhaniah (Faculty of Business Management, University Teknologi MARA, 2018)
Malaysian Code of Corporate Governance (MCCG) was introduced after the Asian Financial Crisis in 1997 as it became one of the major concern in many countries. The events of corporate collapses and financial crisis have made to realisation that having a corporate governance practices is crucial. Hence, Bursa Malaysia has introduced the code as one of the listing rules. One of the objectives of MCCG is to recognise the best framework for principles and best practices in corporate governance. Also, it could aid in providing investors with equivalent access to value important corporate information. Issues related to corporate governance is not new as it was developed with the birth of corporation. However, this issue only received significant attention due to the wave of CEO dismissals in the first half of 1990s and after the massive bankruptcies of Enron and World.com in the early 2000s. Due to a crises and collapses happened, many has realised the importance of corporate governance in the operation of a firm. Previous studies have shown that there are mixed relationships between corporate governance and firm's performance. Thus, this study aims to identify the relationship between corporate governance practices and firm performance among the top 30 public listed companies in Malaysia from 2013 to 2016. The determinants of corporate governance that are being used in this study are board size, board independence, audit committee and board meetings. The performance of the firm is measure by its return on assets. Based on the findings, it was found that board size, board independence and board meetings have a significant negative relationship with ROA while audit committee has a significant positive relationship with ROA.